2020
DOI: 10.1108/jcre-06-2019-0029
|View full text |Cite
|
Sign up to set email alerts
|

Identifying the criteria for corporate real estate decisions through the laddering technique: an analysis of care organisations in The Netherlands

Abstract: Purpose Board members and real estate managers (decision makers) play an important role in the decision-making process in nursing home organisations. This study aims to provide an understanding of underlying attributes and benefits sought by decision makers when making nursing home real estate decisions. Design/methodology/approach Decision makers from seven different nursing home organisations in The Netherlands were interviewed using the laddering technique to determine the individual requirements, the con… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

0
4
0

Year Published

2021
2021
2024
2024

Publication Types

Select...
4

Relationship

0
4

Authors

Journals

citations
Cited by 4 publications
(4 citation statements)
references
References 24 publications
0
4
0
Order By: Relevance
“…The investment in real estate in nursing homes in Europe has grown, given the region’s increasing population of elderly individuals. A study by Huisman et al revealed that decision makers in the area aim at improving the life quality and satisfaction of individuals in nursing homes by including residents and staff in the decision-making processes of increasing investments in real estate [ 29 ]. Kazak et al argued that countries in Western Europe had begun raising the old-age category from 65 to ensure that the older generations engage in communal and societal activities while having improved physical health compared with previous generations [ 30 ].…”
Section: Resultsmentioning
confidence: 99%
See 1 more Smart Citation
“…The investment in real estate in nursing homes in Europe has grown, given the region’s increasing population of elderly individuals. A study by Huisman et al revealed that decision makers in the area aim at improving the life quality and satisfaction of individuals in nursing homes by including residents and staff in the decision-making processes of increasing investments in real estate [ 29 ]. Kazak et al argued that countries in Western Europe had begun raising the old-age category from 65 to ensure that the older generations engage in communal and societal activities while having improved physical health compared with previous generations [ 30 ].…”
Section: Resultsmentioning
confidence: 99%
“…In the USA, the need to retrofit existing homes to meet the increasing demands of the elderly population is essential for ensuring quality care [ 25 ]. In Europe, the main reason why real estate investors should consider nursing homes in the region is the tendency of the area to ignore the needs of older individuals, especially during pandemics [ 29 ]. Therefore, these statistics imply that both localities will increase real estate development in healthcare to deal with the lingering challenges in nursing homes by developing establishments that do not focus on profits but deliver quality care to older people.…”
Section: Discussion and Analysismentioning
confidence: 99%
“…Previous studies on CRE decision making [e.g. [23][24] showed that interviews with the so-called laddering technique are a good way to get insight in thought processes. Laddering is a qualitative research technique which can be used to understand opinions, attitudes, and beliefs of individuals' [25].…”
Section: Methodsmentioning
confidence: 99%
“…Recent 5IR talks have sparked research interest in ways to ensure “harmonious human-machine collaborations, focusing on the wellbeing of multiple stakeholders (society, companies, employees, customers)” (Noble et al , 2022), suggesting an increased focus on impacts on stakeholders’ well-being and liveability since they contribute to organisational performance. Understanding how to obtain benefits from new developments with a minimal negative impact on costs or efficiency (Huisman et al , 2021). Digital technologies are aligned with FM’s well-being and innovation goals and provide opportunities for the management of operations for greater efficiency and cost reduction (Ensafi and Thabet, 2021).…”
Section: Introductionmentioning
confidence: 99%